Inference Markers in Conversation: a German-Italian Comparative Analysis - Ravetto, Miriam (ANNALI. SEZIONE GERMANICA. Rivista del Dipartimento di Studi Letterari, Linguistici e Comparati dell’Università degli studi di Napoli L’Orientale, 2021)
The term inference generally refers to the expression of predictions during discourse processes using information given by interactants in previous turns. Authentic data show that (adverbial) connectives are often used to introduce conversational turns containing an inference. The main purpose of the present work is to provide a comparison between the markers of inference in spoken German and Italian. Using the methodological approach of the conversational analysis and the interactional linguistics, the research focuses on four connectives frequently attested to introduce inferences: German dann, also and Italian allora, quindi. The paper highlights some conversational and syntactic features of these connectives as well as their functions. The analysis is based on a corpus of 10 spontaneous conversations from the Korpus FOLK and 15 talkshow-interactions for the investigation of the German language and on 5 interactions and 10 Talkshow-Conversation for the study of Italian data.